ChemInform Abstract: Cobalt Catalyzed C—H and N—H Bond Annulation of Sulfonamide with Terminal and Internal Alkynes. Issue 18 (April 2016) - Kalsi, Deepti; Sundararaju, Basker
Abstract: An efficient procedure is elaborated for the Co‐catalyzed oxidative annulation of sulfonamides with alkynes leading to benzothiazine derivatives with high regioselectivity and excellent functional group tolerance.